HUBUNGAN ANTARA PENDAMPING PERSALINAN DENGAN KELANCARAN PROSES PERSALINAN KALA II DI PUSKESMAS TAMBUSAI KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - masdi janiarli (Jurnal Maternitas Kebidanan, 2018)
Maternal mortality rates (MMR) in Indonesia is the highest compared with MMR in other ASEAN countries. One reason is the lack of family roles, especially their husbands in the delivery process. Indonesia Demographic and Health Survey (IDHS) in 2007, maternal mortality rate 228 per 100,000 live births. The direct causes of maternal deaths related to pregnancy and childbirth in particular are bleeding (28 percent). While the maternal mortality rate in DIY in 2007 that is 105/100.000 live births and is targeted to be 87.5 / 100,000 live births in 2013. To determine the relationship between labor companion to the smooth process of second stage of labor in di Puskesmas Tambusai. The study deskriptif analytic. The study design was cross sectional. The number of samples is 45 samples using total sampling technique. The data collected, processed and analyzed using the statistical test Chi Square (X2) with 95% confidence level. Complementary delivery most husbands (53,33%). Second stage of labor process most current (57,78%). There is a relationship between labor companion to the smooth process of second stage of labor in di Puskesmas Tambusai p <0.05 (p = 0.002) with the closeness of the relationship is (KK = 0.420). There is a relationship between the companion labor with phase II of labor process in di Puskesmas Tambusai.